Histone methyltransferase SETDB1 promotes cells proliferation and migration by interacting withTiam1 in hepatocellular carcinoma - Zhang, Yuqin (BMC Cancer, 2018)
BACKGROUND: SETDB1 is a histone H3K9 methyltransferase, which plays a significant role in the occurrence and progression of tumors. Previous studies have confirmed that T-lymphom invasion and metastasis gene (Tiam1) is a protein associated with the metastasis of hepatocellular carcinoma (HCC); however, we have not yet been successful in elucidating the specific mechanism of HCC. METHODS: Yeast two-hybrid test was conducted to screen proteins that interacted with Tiam1 gene. Glutathione-S-transferase (GST) pull-down and crosslinking-immunoprecipitation (CLIP) assays were performed to determine whether SETDB1 can interact with Tiam1 gene. A series of related experiments were performed to explore role of SETDB1 on cell proliferation, migration, and invasion in HCC. Recovery experiment was performed to investigate the effect of Tiam1 knockdown on cell proliferation and migration, which was caused by SETDB1 overexpression in HCC cells. The expression of SETDB1 was frequently upregulated in HCC tissues and positively correlated with Tiam1. RESULTS: GST pull-down and CLIP assays were performed to elucidate the interaction between SETDB1 and Tiam1. Cell proliferation, migration, and epithelial mesenchymal transformation (EMT) in HCC cells was promoted with the overexpression of SETDB1. Following the knockdown of Tiam1 gene, the effect of SETDB1 on cell proliferation and migration was reversed in HCC cells. The expression of SETDB1 was frequently up-regulated in HCC tissues, and it was positively correlated with Tiam1 gene. CONCLUSIONS: Ours is the first study to prove that SETDB1 promotes the proliferation and migration of cells by forming SETDB1-Tiam1 compounds. We found that SETDB1-Tiam1 compounds were involved in a novel pathway, which regulated epigenetic modification of gene expression in HCC samples. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-018-4464-9) contains supplementary material, which is available to authorized users.